Assessing the impacts of Lantana camara and opportunities for ecological restoration after its removal: does clearing facilitate both soil and native vegetation recovery? - Bolosha, Uviwe (Rhodes University, Faculty of Science, Department of Environmental Science)
Invasive alien plants (IAPs) are one of the major contributing factors to biodiversity loss, and Lantana camara is among the top ten alien invaders worldwide. Lantana camara threatens native biodiversity and human health, prevents natural succession, and has an economic and environmental impact globally. With current climate change and future predictions, these IAPs are anticipated to continue posing huge threats to ecosystem composition, structure, and function. Even though L. camara is a widespread IAP, there is still limited knowledge in South Africa on how it influences soil physicochemical properties at the species level, vegetation communities, and soil seed banks at the community level following its invasion. There is also minimal knowledge on the management and control (i.e., clearing for restoration purposes) of L. camara in South Africa, especially in the Eastern Cape province of South Africa. To address the knowledge gap, this thesis was structured into three main aspects: understanding L. camara invasion mechanisms, evaluating invasion impacts on both the aboveground and belowground communities, and invasion management. The main objectives of this thesis were (i) to examine how L. camara invasion (at a species level) affected soil physicochemical properties across different seasons, (ii) to assess how L. camara influences natural vegetation (at a community level), (iii) to examine the effects of L. camara invasion (at the community level) on belowground soil seed banks and also assess the availability of pioneer native species and IAPs in the soil seed banks, and (iv) to evaluate soil and vegetation responses following L. camara clearing in comparison to invaded and uninvaded conditions. To answer these objectives, different studies were carried out in the Eastern Cape province, South Africa, on various farms within the Albany Thicket Biome. The results (Chapter 3) show that L. camara alters and modifies some soil physical properties, such as soil infiltration rate, repellency, and soil penetration resistance, in the communities it invades. A significant decrease in soil penetration under the L. camara canopy was observed compared to soils from the edge and out position. Moreover, significantly faster infiltration rates were observed in the canopy and edge positions than in the out position. The study also observed that these modifications in soil physical properties vary depending on the season. A seasonal comparison in soil penetration showed that soil was more compact in the dry season than the wet season, and significantly faster infiltration rates were observed in summer than in the other seasons. The soil collected under the invaded sampling positions was mostly wettable (80"“100%), and not strongly, severely, or extremely repellent across all the seasons. The changes in soil properties caused by L. camara could create favourable conditions for its growth and invasion. Seasonal changes in soil properties also highlight how environmental conditions, especially temperature and rainfall patterns, can affect soil physical properties. The findings in Chapter 4 observed both the negative and positive impacts of L. camara, where the species did not have negative effects on species richness, diversity, or cover of some native species growth forms (i.e., graminoids and forbs). For all species, both species richness and Shannon-Wiener (H') were significantly higher in the L. camara invaded condition compared to the uninvaded condition. The Simpson's (J') and Pielou's evenness (D') indices, however, showed no differences between the invasion conditions. Furthermore, the effects of L. camara on vegetation cover were growth form-dependent, with differences being noted for trees and shrubs but not for graminoids and forbs. Changes in vegetation structure and composition were also noted where L. camara created favourable conditions for some species to co-occur with it, meaning that its known trait of changing soil physicochemical properties could benefit some species. Generally, the results of this study showed that the effects of L. camara on vegetation are varied and do not have a predictable pattern, so they should not be generalised. The findings (Chapter 5) also indicate that the L. camara invasion had a negative impact on seedling abundance and composition but not species diversity and richness. This is evident through the decrease in seedling abundance of forbs and graminoids in the L. camara invaded condition. Lantana camara also acted as a refuge for some plant species, mostly native forbs and grasses, including Aptenia cordifolia, Chamaesyce prostrata, Oxalis spp., and Setaria spp., as well as alien forbs such as Bidens pilosa, Plantago lanceolata, and Taraxacum officinale, suggesting L. camara does not entirely eliminate less competitive plant species but can co-exist with them. Lantana camara also displaced some native species, and this could be associated with their displacement in the standing vegetation. Moreover, the species also displaced the seed banks of some alien species, thus showing its competitive ability. Overall, L. camara invasion negatively influenced soil seed bank seedling abundance and composition of some species, but not diversity and richness. The results in Chapter 6 indicated that clearing L. camara is an effective method for reducing its population. However, our findings suggest that clearing alone may not be enough to re-establish these communities with native species. This is because the results of this study showed varied changes in soil properties and native vegetation (species richness, species diversity, percentage cover, and composition) after L. camara clearing. For example, soil moisture and soil penetration resistance showed no significant differences among the invasion conditions; only monthly variations were observed. This is an indication that seasonality influenced these properties. Significantly lower soil infiltration rates were observed in the cleared condition compared to the other conditions and were influenced by the months and the interaction of the clearing conditions and months. The water droplet penetration time showed no significant difference among the clearing conditions over the three months, and all the soil collected from the three clearing conditions was mostly wettable. Soil chemical properties showed that the L. camara invaded and cleared conditions had significantly lower soil pH compared to the uninvaded condition, and an increase in soil pH was observed after clearing L. camara. Vegetation characteristics showed that both the Shannon-Wiener index (H') and the Simpson's index (D') were lower in the invaded and cleared conditions compared to the uninvaded condition, and significant differences were observed. A slight increase in the H' and D' indices was also observed after clearing L. camara. The mean percentage cover for trees and shrubs was significantly higher in the invaded condition than in the cleared and uninvaded conditions. However, the mean percentage cover of forbs and graminoids was similar among the invaded, cleared, and uninvaded conditions, and no significant differences were observed. When L. camara was cleared, native species recovery was observed and was more notable in the understory species. Overall, some signs of vegetation recovery were observed, although challenges such as secondary invaders and re-invasion by L. camara were noted in the cleared areas. This chapter then concluded that active restoration interventions should be incorporated during restoration to fast-track soil and vegetation recovery. The findings of this thesis will make several significant contributions to the field of biological invasions and provide baseline information that can be used in future studies. These are discussed in the various research chapters. Overall, the thesis concludes that L. camara invasion has varied impacts on native vegetation and soil, and its clearance, should be prioritised to reduce the negative impacts. However, L. camara cleared areas (by WfW in South Africa) require follow-up and monitoring at an early stage to assess vegetation and soil restoration success. In addition, active management measures after L. camara's removal should be considered for clearing programmes to yield positive ecosystem recovery.,Thesis (PhD) -- Faculty of Science, Environmental Science, 2024
Keywords: Lantana camara; Restoration and conservation; Restoration ecology; Invasive plants; Physicochemical process; Soil seed banks; Invasion driver